Export Competitiveness Of Bananas (Musa) Indonesia In The Asean Market - Ramadhan, Andika Wahyu; Yoesdiarti, Arti; Miftah, Himmatul (Universitas Djuanda, 2024)
The objectives of the study were to determine the export performance and analyze the comparative and competitive advantages of Indonesian bananas compared to competing countries in the ASEAN market. The study used time series observation data from various sources including FAOSTAT and Trade Map which ranged from 2012 to 2021. The analysis method in the research is using descriptive analysis, Revealed Comparative Advantage analysis, and Trade Specialization Index analysis. The result of the research is that Indonesian bananas have a lower export value compared to the Philippines, Malaysia and Vietnam. The Philippines is comparatively superior in banana exports to the ASEAN market, while Indonesia, Malaysia, and Vietnam have lower comparative competitiveness. The role in banana trade in the ASEAN market varies between countries. In banana trade, Indonesia and the Philippines are competitively superior countries with strong exporter values, while Malaysia and Vietnam are not competitively superior as they experience fluctuating values.